2015
DOI: 10.3341/kjo.2015.29.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Deep Anterior Lamellar Keratoplasty Using Irradiated Acellular Cornea with Amniotic Membrane Transplantation for Intractable Ocular Surface Diseases

Abstract: PurposeTo report the clinical outcomes of deep anterior lamellar keratoplasty (DALK) when sterile gamma-irradiated acellular corneal tissues (VisionGraft) are used in combination with amniotic membrane transplantation (AMT) for intractable ocular surface diseases.MethodsThe medical records of fifteen patients who had DALK with AMT were retrospectively reviewed. Indications for surgery included ocular burn, bacterial keratitis, herpes simplex virus keratitis, corneal opacity with Stevens-Johnson syndrome, Moore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…γ-ray irradiation works by directly destroying DNA and causing indirect damage via reactive oxygen species (ROS) generation 26, 27 . Recent studies have reported that the γ-irradiated sterile decellularized cornea can be effectively applied to lamellar keratoplasty 2830 . The combined use of polyethylene glycol and γ-ray irradiation makes the maximal decelluarization effect, because neither porcine endogenous retroviral DNA sequence nor alpha-1,3 galactose epitope was detected after treatment 31 .…”
Section: Discussionmentioning
confidence: 99%
“…γ-ray irradiation works by directly destroying DNA and causing indirect damage via reactive oxygen species (ROS) generation 26, 27 . Recent studies have reported that the γ-irradiated sterile decellularized cornea can be effectively applied to lamellar keratoplasty 2830 . The combined use of polyethylene glycol and γ-ray irradiation makes the maximal decelluarization effect, because neither porcine endogenous retroviral DNA sequence nor alpha-1,3 galactose epitope was detected after treatment 31 .…”
Section: Discussionmentioning
confidence: 99%
“…GI has also been applied successfully to human corneas. Most of patients that received a gamma irradiated human cornea showed favorable outcomes without graft rejection, loss of transparency or neovascularization [30]. Moreover, GI might reduce allogenicity [31], with the added advantage of a shelf life of the sterile irradiated human cornea for more than one year at room temperature [32].…”
Section: Introductionmentioning
confidence: 99%
“…In fact sterile corneas may provide better visual acuity for anterior lamellar procedures due to a smoother interface than do fresh tissues for laser-assisted lamellar anterior keratoplasty 21. Wee et al 22 reported excellent outcomes when using the combination of irradiated acellular cornea with amniotic membrane transplantation (AMT) in patients with intractable ocular surface diseases. They noted that AMT facilitated epithelial healing, and ultimately better graft survival.…”
Section: Discussionmentioning
confidence: 99%